siAKR1C3@PPA complex nucleic acid nanoparticles inhibit castration-resistant prostate cancer in vitro - Cui, Xiaoli; Yao, Zhou; Zhao, Tianyu; Guo, Jiahui; Ding, Jipeng; Zhang, Siwei; Liang, Zuowen; Wei, Zhengren; Zoa, Alexis; Tian, Yuantong; Li, Jing (Frontiers in Oncology, 2022)
Introduction: AKR1C3, as a crucial androgenic enzyme, implicates the androgen biosynthesis and promoting prostate cancer cell growth in vitro. This study provides a new gene therapy strategy for targeting AKR1C3 to treat CRPC. Methods: siAKR1C3@PPA is assembled from PEG3500, PAMAM, Aptamer-PSMA, and siRNA for AKR1C3. We analyzed the relationship between AKR1C3 expression and the survival rate of prostate cancer patients based on the GEPIA online database to perform disease-free survival, and found that AKR1C3 may be an important factor leading to poor prognosis in prostate cancer. Considering AKR1C3 as a therapeutic target for castration-resistant prostate cancer (CRPC), we constructed a complex nucleic acid nanoparticle, siAKR1C3@PPA to investigate the inhibitory effect on CRPC. Results: Aptamer-PSMA acts as a target to guide siAKR1C3@PPA into PSMA-positive prostate cancer cells and specifically down regulate AKR1C3. Cyclin D1 was decreased as a result of siAKR1C3@PPA treatment. Changes in Cyclin D1 were consistent with decreased expression of AKR1C3 in LNCaP-AKR1C3 cells and 22RV1 cells. Furthermore, in the LNCaP-AKR1C3 group, 1070 proteins were up-regulated and 1015 proteins were down-regulated compared to the LNCaP group according to Quantitative 4D label-free proteomics. We found 42 proteins involved in cell cycle regulation. In a validated experiment, we demonstrated that PCNP and CINP were up-regulated, and TERF2 and TP53 were down-regulated by western blotting. Conclusion: We concluded that siAKR1C3@PPA may arrest the cell cycle and affect cell proliferation.